Monitoring and Evaluation of Health System Strengthening: Iceida’s Development Collaboration in Monkey Bay, Malawi, in 2000-2014 - Jónína Einarsdóttir; Geir Gunnlaugsson (Nordicum-Mediterraneum, 2016)
The Icelandic International Development Agency (Iceida) supported the health services in the Monkey Bay area in Mangochi district in Malawi in southern Africa in the period 2000-2011. It included construction of physical structures, logistic, training of health staff, and community health activities. One additional feature included support for the national electronic Health Monitoring Information System (HMIS) in place, with extraction and analysis of data generated by the health services in the area. In this paper, the development of the services will be analysed and discussed. Further, difficulties to find appropriate indicators to monitor health services, in Monkey Bay and elsewhere, will be presented and elaborated upon.